Korupsi di era Pandemi Covid-19 - Ardiyanti Aris (Jurnal Litigasi Amsir, 2022)
This study aims to find the factors that cause corruption crimes during the Covid-19 pandemic and forms of corruption prevention during the Covid-19 pandemic. This research uses normative research with a statutory approach and a comparison approach. Types and sources of legal materials use primary, secondary, and tertiary legal materials. Data analysis will be studied with deductive logic reasoning because normative legal research uses logical analysis, argumentation, and perspective, so this research is qualitative. The results showed that legal factors could cause corruption crimes during the Covid-19 pandemic because there are weaknesses in laws and regulations, including inadequate quality legislation, lenient sanctions, and inconsistent and indiscriminate execution of penalties. The form of preventing corruption crimes during the Covid-19 pandemic is by increasing supervision to minimize the opportunity for corruption behaviour to occur following the KPK Circular Letter KPK Number 8 of 2020 related to the prevention of corruption crimes and government officials should have an appropriate attitude as a government official to guarantee transparent and accountable implementation in realizing good government.